Effect of Nutmeg Flesh (Myristica fragrans Houtt) against Streptococcus mutans growth - Putri Rahmi Noviyandri; Nurhadisah Nurhadisah; Santi Chismirina (Journal of Syiah Kuala Dentistry Society, 2020)
Streptococcus mutans is an oral commensal. Its bacteria are involved in the dental caries pathogenesis. Nutmeg flesh (Myristica fragrans Houtt) is one of the native plants of Indonesia. Nutmeg flesh (Myristica fragrans Houtt) contains antibacterial properties such as alkaloids, flavonoids, tannins, terpenoids, saponins, and essential oil. The purpose of this study is to determine the effect of nutmeg flesh (Myristica fragrans Houtt) extract in the inhibition of Streptococcus mutans growth. The extract of nutmeg flesh (Myristica fragrans Houtt) was made using the maceration method with ethanol 96% as the solvent. The Diffusion methods to identify the inhibition of Streptococcus mutans growth. The concentration of nutmeg flesh (Myristica fragrans Houtt) extract used in this study were 25%, 50%, 75%, and 100. The one-way ANOVA analysis showed that there was the effect of nutmeg flesh (Myristica fragrans Houtt) extract on Streptococcus mutans growth with value p0.05, and then data was tested by Least Significant Difference (LSD). This study's conclusion showed an effect of nutmeg flesh (Myristica fragrans Houtt) extract in inhibiting Streptococcus mutans growth. The concentration of nutmeg flesh (Myristica fragrans Houtt) extract, which has the greatest inhibition zone on the growth of Streptococcus mutans, is at a concentration of 100% is 33,53 mm